Laser-induced breakdown spectroscopy acoustic testing of the Mars 2020 microphone. (January 2019) - Murdoch, N.; Chide, B.; Lasue, J.; Cadu, A.; Sournac, A.; Bassas-Portús, M.; Jacob, X.; Merrison, J.; Iversen, J.J.; Moretto, C.; Velasco, C.; Parès, L.; et al.
Abstract: The SuperCam instrument suite onboard the Mars 2020 rover will include the Mars Microphone, an experiment designed to record the sounds of the SuperCam laser strikes on rocks and also aeolian noise. In order to record shock waves produced by the laser blasts, the Mars Microphone must be able to record audio signals from 100 Hz to 10 kHz on the surface of Mars, with a sensitivity sufficient to monitor a laser impact at distances up to 4 m. The Aarhus planetary simulator facility has been used to test the Mars 2020 rover microphone in a controlled Martian environment. The end-to-end tests performed in a 6 mbar CO2 atmosphere, with wind, and also with the microphone at −80° C have demonstrated that the SuperCam/Mars Microphone requirements are satisfied. Tests were also performed on Martian soil simulant targets showing that the variation of the acoustic energy of the shock wave depends on the level of compaction of the target.